2010
DOI: 10.1177/0886260510372935
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Child Sexual Abuse as Predictors of Later Sexual Victimization

Abstract: The association between a history of child sexual abuse (CSA) and specific negative outcomes (attachment, feelings of power, and self-esteem) was explored as was the relationship between those negative outcomes and sexual victimization during the first semester of college. Two groups of freshman college women (67 who had experienced CSA and 55 who had not) completed measures of attachment, feelings of power, and self-esteem at the beginning of their freshman year of college. At the end of their first semester … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 34 publications
(53 reference statements)
2
18
0
4
Order By: Relevance
“…These findings are consistent with those of the only previous study that has assessed revictimization and attachment anxiety: Reese-Weber and Smith [46] identified attachment anxiety as an important predictor of revictimization. As Nurius [78] pointed out, from an individual perspective, there are always relative costs of both taking and not taking a specific action in a specific situation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with those of the only previous study that has assessed revictimization and attachment anxiety: Reese-Weber and Smith [46] identified attachment anxiety as an important predictor of revictimization. As Nurius [78] pointed out, from an individual perspective, there are always relative costs of both taking and not taking a specific action in a specific situation.…”
Section: Discussionsupporting
confidence: 91%
“…Two recent studies on attachment anxiety have reported a positive correlation between child sexual abuse and attachment anxiety in adulthood [45], [46]. Moreover, a prospective study on predictors of revictimization [46] found that attachment anxiety plays an important role in later revictimization.…”
Section: Introductionmentioning
confidence: 99%
“…In hearing populations, another outcome of child sexual trauma is elevated probability of adult sexual trauma in both male and female populations (Aosved, Long, & Voller, 2011;Reese-Weber & Smith, 2011). These results have often been attributed to the traumagenic dynamics described by Finkelhor and Browne (1985), that is, early sexual trauma results in the development of traumatic sexualization, betrayal, powerlessness, and stigmatization.…”
mentioning
confidence: 91%
“…This study aims to replicate the procedures from a previous study conducted by Reese-Weber and Smith (2011). These researchers examined variables in the context of the Traumagenic Dynamics Model and investigated their relationship to revictimization in the first semester of college.…”
Section: Traumagenic Dynamics Modelmentioning
confidence: 98%
“…Unfortunately, for the victims of childhood sexual abuse the victimization is not always confined to childhood. Research indicates that survivors of childhood sexual abuse are more likely to be revictimized later in life than those who were not sexually abused as children (Messman & Long, 2000;Polusny, Rosenthal, Aban, & Follette, 2004;Reese-Weber & Smith, 2011). One study found that victims of childhood sexual abuse were not only at higher risk for sexual assault or abuse later in life, but also for physical abuse, kidnapping and stalking (Widom, Czaja, & Dutton, 2008).…”
mentioning
confidence: 99%